Abnormally low regional cerebral oxygen saturation after induction of anesthesia without neurological abnormality: A case report - Jun Honda; Shiori Tanaka; Keisuke Yoshida; Satoki Inoue (Annals of Cardiac Anaesthesia, 2023)
Measurement of regional cerebral oxygen saturation (rSO2) using near-infrared spectroscopy (NIRS) in cardiac surgery is known to be useful in reducing postoperative neurological complications. We here present a case of a 71-year-old man in whom severe decrease in unilateral rSO2 was observed after induction of general anesthesia for percutaneous mitral valve clipping, although no neurological abnormalities were found. NIRS does not always predict postoperative neurological complications.